Template-free synthesis of bubble-like graphitic carbon nitride for photocatalytic CO2 reaction - Muhammad Afiq Mohamad Mansor (2017)
Graphitic carbon nitride (g-C3N4) has emerged as a promising and attractive choice as a photocatalyst in the photocatalytic reaction of reducing CO2 into solar fuels which represents a potential solution to global warming. While other semiconductors such as TiO2 have been explored, its absorbance is limited to the UV region unlike g-C3N4, which is active in visible light. g-C3N4 however, has poor selectivity in CO2 reduction where reduction of protons to hydrogen gas is a dominant competing reaction that inhibits CO2 reduction reactions. The purpose of this project is to fabricate amine-functionalised g-C3N4 to enhance the selectivity of g-C3N4 for CO2 reduction. g-C3N4 samples were synthesized via template-free solvothermal synthesis from cyanuric chloride and varying amounts of diethylenetriamine. Characterisation of the samples via SEM, TEM and UV-Vis DRS was carried out to investigate their morphology, absorbance, and band gap. A template-free synthesis of “bubble-like” g-C3N4 was reported through the copolymerization of cyanuric chloride and diethylenetriamine via solvothermal route. Photocatalytic CO2 reduction was carried out for the diethylenetriamine-modified gC3N4 samples and a pristine g-C3N4 sample as reference after loading them with platinum co-catalyst. The result showed that CO2 reduction with the diethylenetriamine-modified g-C3N4 samples produced higher amounts of CH4 and CO than CO2 reduction with pristine g-C3N4 in which H2 was the main product. This is attributed to the addition of basic amine groups from diethylenetriamine which enhanced the adsorption of CO2 on to g-C3N4 surface. The addition of amine groups from diethylenetriamine not only enhances selectivity of g-C3N4 for CO2 reduction. It also enhances light absorption in UV region. The exploration and understanding of the formation mechanism of bubble-like morphology is still under study. Future studies could explore methods to synthesize porous nano-bubbles that could provide larger surface area and surface active sites. Other co-catalysts and hole scavengers used in CO2 reduction could also be explored in future projects or studies.